The Role of Digital Academic Supervision in Enhancing Teacher Professionalism in the Era of Industry 4.0: A Literature Reviews - Hurriyati, Hurriyati; Hadiyanto, Hadiyanto; Sulastri, Sulastri (Postgraduate School, Universitas Negeri Padang, 2024)
This study aims to evaluate the effectiveness of digital-based academic management in enhancing teacher professionalism and improving the quality of education in the context of the Industrial Revolution 4.0. Using a literature reviews method, the study analyzes references from academic journals, books, and credible online sources to understand the challenges and opportunities of digital academic supervision. Descriptive analysis is employed to synthesize findings and identify implications. The results highlight that digital academic supervision is a critical innovation for integrating technology into education. It enables administrators to train teaching staff, fostering professional development and ICT competence. However, challenges include inadequate knowledge of technology among school leaders, limited infrastructure in remote areas, and resource deficiencies. Before the COVID-19 pandemic, traditional supervision methods were dominant, requiring physical visits and manual observation. In contrast, the current digital approach is more efficient, enabling remote supervision and fostering professional collaboration through online platforms. Despite its potential, successful implementation requires robust infrastructure, ongoing training, and a supportive digital ecosystem. This study concludes that digital academic supervision is a transformative tool for addressing the demands of Industry 4.0, with significant implications for teacher development and educational quality improvement.